2019
DOI: 10.1002/ijc.32571
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a seven‐immune‐feature‐based prognostic score for oral squamous cell carcinoma after curative resection

Abstract: Immune infiltrates have been increasingly recognized as robust prognostic factors for human cancer. Here, we developed and validated a seven‐immune‐feature‐based prognostic score (7IFBPS) for patients with oral squamous cell carcinoma (OSCC) after curative resection. Fourteen immune features regarding detailed locations and densities of seven types of tumor‐infiltrating immune cells (TIIs) were characterized in clinical samples from 269 eligible patients in three independent cohorts by immunohistochemistry cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 50 publications
(144 reference statements)
1
27
0
Order By: Relevance
“…1 Although various genetic or epigenetic biomarkers in OSCC have been proposed for prognostic assessment including microRNA, lncRNA and alternative mRNA splicing signature, they are still far from optimal. 20,22,23 In addition to these intrinsic features of cancer itself, tumor-infiltrating immunocytes have been established as key drivers underlying tumorigenesis as well as novel biomarkers with tremendous diagnostic and prognostic significance. 4,6 Here, we determined the location and amount of MDSCs in OSCC and revealed that high amount of CD11b + MDSCs associated with inferior survival and quantification of CD11b + MDSCs might be a novel independent prognostic factor for OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although various genetic or epigenetic biomarkers in OSCC have been proposed for prognostic assessment including microRNA, lncRNA and alternative mRNA splicing signature, they are still far from optimal. 20,22,23 In addition to these intrinsic features of cancer itself, tumor-infiltrating immunocytes have been established as key drivers underlying tumorigenesis as well as novel biomarkers with tremendous diagnostic and prognostic significance. 4,6 Here, we determined the location and amount of MDSCs in OSCC and revealed that high amount of CD11b + MDSCs associated with inferior survival and quantification of CD11b + MDSCs might be a novel independent prognostic factor for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The density of CD11b + MDSCs in OSCC specimens was recorded independently at CT and IM and presented as the mean of positively stained cells per mm 2 , similar to our previous report. [18][19][20] As shown in Figure 1, cell counts of CD11b + MDSCs were automatically quantified using ImageJ (version 2.0). The optimal cut-off values for the densities of CD11b + MDSCs at CT and IM were determined after analyzing the association between cell amount and overall survival (OS) by X-tile software with a minimum P value approach (version 3.6.1, https://medicine.yale.edu/lab/rimm/research/software/).…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…In two studies, immunoscore only included TILs, and more precisely CD3 + and CD8 + cells (Lechner et al 2017;Zhang et al 2018). A recent study con rmed the positive prognostic impact of TILs in oral squamous cell carcinomas by increasing the immune signature to seven markers that can predict patient survival (Zhou et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For oral carcinoma, identification of immune feature-based prognostic score has been recently introduced by Zhou et al. ( 38 ) who reported a promising prognostic value for an immunoscore based on the evaluation of CD3 in central areas and at invasive margins of OSCC; CD8, CD45RO, and FOXP3 in the central part of OSCC; FOXP3 and CD45RO at invasive margins of OSCC. However, the proposed immunoscore for OSCC will require further validation.…”
Section: Immunoscore For Osccmentioning
confidence: 99%
“…The most promising results with immunoscore have been reported in colorectal cancer where a scoring system for the quantification of CD3 and CD8 were standardized and showed a promising predictive power superior to TNM staging system (36) and showed successful results in phase 3 clinical trials (37). For oral carcinoma, identification of immune feature-based prognostic score has been recently introduced by Zhou et al (38) who reported a promising prognostic value for an immunoscore based on the evaluation of CD3 in central areas and at invasive margins of OSCC; CD8, CD45RO, and FOXP3 in the central part of OSCC; FOXP3 and CD45RO at invasive margins of OSCC. However, the proposed immunoscore for OSCC will require further validation.…”
Section: Immunoscore For Osccmentioning
confidence: 99%